Chloroplast DNA diversification of Malaysian Pineapple - Hamdan, Norfadilah (2013)
There are several genes are normally used for the phylogenetic study such as Mitochondria DNA (mtDNA), Chloroplast DNA (cpDNA) and Nuclear DNA (nDNA). Among these three genomes, cpDNA is commonly being used in phylogenetic study because it is easy to amplify via PCR, evolves at a conservation rate and it has appropriate length and base substitution rate for inferring phylogeny at higher levels. In this study, phylogenetic tree of eight Malaysian pineapple (Ananas comosus) cultivars were constructed using sequences of large subunit of the ribulose- bisphosphate carboxylase (rbcL) gene. A rbcL gene was isolated from genomic DNA, amplified and sequenced. Phylogenetic analysis was carried out using maximum parsimony method. Results revealed that rbcL gene of Ananas comosus is about 1250 bps. Based on the tree, eight Malaysian pineapple cultivars were classified into two groups. The first group consisted of Yankee and Gandul cultivars while second group consisted of Moris, Moris Bentanggur, Moris Gajah, N36, Josaphine and Sarawak. Bootstrap value in some branches were low this is reflected by the small number of informative characters (981 were conserved and 85 were potentially informative) to build the tree. Formation of several group or subclades is due to its similar genetic pattern, thus support this system classification. The study suggested that rbcL gene could be used to determine the phylogenetic relationship distinguish the pineapple cultivars